TUGAS DAN FUNGSI DINAS KESEHATAN KOTA SEMARANG DALAM MEMBERIKAN PELAYANAN JAMKESMAS, KHUSUSNYA DI KECAMATAN TEMBALANG - Irma Cahyaningtias, Amiek Soemarmi, Budi Goetami (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Healthcare is a right, and investment, and all citizens are entitled to health care, including the poor and people in need.Needed a system that regulates the implementation for fulfilling the rights of citizens to obtain social welfare, the health services, because health is very important to perform an activity in order to earn a decent living, the Semarang City Health Office provide free medical treatment. Jamkesmas is the Community Health Insurance provided by the City of Semarang to the poor and people who are not able to certain conditions, the study entitled